2009
DOI: 10.1007/s00024-004-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Glacio–isostatic Adjustment in the Po Plain and in the Northern Adriatic Region

Abstract: Vertical movements in the Po plain (northern Italy) are controlled by natural and anthropogenic effects. Since Italy is located in the far-field of the former late Pleistocene ice sheets, isostatic deformations are primarily driven by melt water loading and represent a major component of long-term natural movements across the entire Mediterranean. In addition to far-field sources, here we consider the isostatic effects of melting of the nearby Würm Alpine ice-sheet, suggesting that it is possible to put bounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…According to Norton and Hampel (2010) post-LGM unloading may result in uplift rates > 10 mm/a during the early stages of the deglaciation (i.e.~20-15 ka), but such values quickly reduce to 0.3-0.4 mm/a after~13 ka, when the viscous deformation becomes dominant with respect to the elastic strain. Slightly lower, but similar values were obtained by Stocchi et al (2005) and Spada et al (2009) based on the sea-level equation approach (Farrell and Clark, 1976). Spada et al (2009), in particular, estimate up to~0.5 mm/a of nearpresent uplift rates due to the deglaciation since the LGM and the melting of the remote ice-sheets in the far-field of the Mediterranean based on the ICE-5G model of Peltier (2004) (Fig.…”
Section: Modeling Results and Interpretationsupporting
confidence: 70%
See 2 more Smart Citations
“…According to Norton and Hampel (2010) post-LGM unloading may result in uplift rates > 10 mm/a during the early stages of the deglaciation (i.e.~20-15 ka), but such values quickly reduce to 0.3-0.4 mm/a after~13 ka, when the viscous deformation becomes dominant with respect to the elastic strain. Slightly lower, but similar values were obtained by Stocchi et al (2005) and Spada et al (2009) based on the sea-level equation approach (Farrell and Clark, 1976). Spada et al (2009), in particular, estimate up to~0.5 mm/a of nearpresent uplift rates due to the deglaciation since the LGM and the melting of the remote ice-sheets in the far-field of the Mediterranean based on the ICE-5G model of Peltier (2004) (Fig.…”
Section: Modeling Results and Interpretationsupporting
confidence: 70%
“…Slightly lower, but similar values were obtained by Stocchi et al (2005) and Spada et al (2009) based on the sea-level equation approach (Farrell and Clark, 1976). Spada et al (2009), in particular, estimate up to~0.5 mm/a of nearpresent uplift rates due to the deglaciation since the LGM and the melting of the remote ice-sheets in the far-field of the Mediterranean based on the ICE-5G model of Peltier (2004) (Fig. S2).…”
Section: Modeling Results and Interpretationsupporting
confidence: 69%
See 1 more Smart Citation
“…TABOO) to validate numerical codes (and vice versa), especially in the case of computation of short-wavelength (or longtime) limits. The challenging issue of the computation of very large degree Love numbers is not addressed in this study, but would deserve an in-depth analysis due to its relevance in regional investigations of glacio-isostasy Spada et al 2009). Recently, Spada et al (2010) have shown that ALMA provides reliable results up to n = O(10 4 ), which however are still awaiting for a validation by means of a code based on the VNM method (TABOO fails for very large n values, see Spada 2008) or on FE.…”
Section: Results For Test 5/1 (Time-domain Love Numbers)mentioning
confidence: 99%
“…Proposed mechanisms of uplift include the isostatic response to the last deglaciation, long-term erosion, detachment of the Western Alpine slab, as well as lithospheric and surface deflection due to sub-Alpine asthenospheric convection (Serpelloni et al, 2013;Nocquet et al, 2016). In the study area the isostatic response to last deglaciation and long-term erosion are characterized by longwavelength sub-mm/a patterns (e.g., Sternai et al 2012;Serpelloni et al, 2013), whereas the elastic response to present deglaciation (Barletta et al, 2006;Spada et al, 2009) shows localized peaks of uplift (up to the mm/a scale) far from the study area. In the Eastern Alps, active shortening contributes to the observed uplift, but the pattern and amount of tectonic uplift due to elastic strain accumulation at faults is still unknown.…”
Section: Introductionmentioning
confidence: 99%